Roles of metal ions in the selective inhibition of oncogenic variants of isocitrate dehydrogenase 1 - Shuang Liu; Martine I. Abboud; Tobias John; Victor Mikhailov; Ingvild Hvinden; John Walsby-Tickle; Xiao Liu; Ilaria Pettinati; Tom Cadoux-Hudson; James S. O. McCullagh; Christopher J. Schofield (Communications Biology, 2021)
Liu et al investigate the effects of divalent metal ions on catalysis and inhibition of the enzyme isocitrate dehydrogenase (IDH) and its cancer-linked variant R132H. They further identify the substrates for IDH as complexes with Mg2+ and show that allosteric inhibitors work by weakening Mg2+ binding of R132H, providing mechanistic insights into the basis for selective R132H IDH1 inhibition.